Relación entre la concentración de hongos con factores ambientales y problemas respiratorios en trabajadores administrativos de la Universidad Nacional de la Amazonía Peruana 2023 - Tuesta Rojas, Cesar Renato (2024)
The study was conducted in the administrative offices of the faculties at the National University of the Peruvian Amazon (UNAP - Iquitos and Zungarococha) during the months of October to December 2023. Through a prospective analytical approach, the relationship between the concentration of fungi in enclosed environments and respiratory problems among administrative staff was assessed, using the precipitation technique on two Petri dishes per environment. The results indicated concentrations of fungi that ranged from intermediate to high in all faculties. Moreover, 91.9% of administrative workers reported respiratory issues in the last week. A statistically significant correlation was established between the concentrations of colony-forming units (CFU) of fungi and the prevalence of respiratory problems. This study highlights the importance of monitoring and controlling air quality in enclosed spaces to prevent respiratory health risks in workplace settings.